Linking experienced barriers during daily travel and transport poverty in peripheral rural areas: the case of Zeeland, the Netherlands - Pot, Felix Johan; Koster, Sierdjan; Tillema, Taede; Jorritsma, Peter (European Journal of Transport and Infrastructure Research, 2020)
People living in peripheral rural areas are often considered to be prone to transport poverty and inaccessibility to activities. Previous identifications of transport poverty have mainly relied on accessibility measures based on land-use and transport data. However, such measures may be very different from how people themselves perceive accessibility. Therefore, explicitly considering perceptions of accessibility may be valuable in evaluating the nature of accessibility issues such as transport poverty. By conducting semi-structured focus group discussions in Zeeland, a rural area of the Netherlands, this paper shows that the mechanisms behind transport poverty are mediated by individual perceptions of accessibility. Local social norms related to accessibility appear to be important in shaping these perceptions. In peripheral rural areas, norms reflecting the dominance of the private car add to the negative appropriation of other transport options and shape expectations with respect to accessibility. Therefore, taking account of perceptions of accessibility, and the ways these are shaped, adds to the understanding of the nature of accessibility issues and is considered vital in designing responsive policies.